2020
DOI: 10.1186/s12889-020-8378-5
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome in indigenous communities in Mexico: a descriptive and cross-sectional study

Abstract: Background: An Amerindian genetic background could play an important role in susceptibility to metabolic diseases, which have alarmingly increased in recent decades. Mexico has one of the highest prevalences of metabolic disease worldwide. The purpose of this study was to determine the prevalence of metabolic syndrome and its components in a population with high Amerindian ancestry. Methods: We performed a descriptive, quantitative, and analytical cross-sectional study of 2596 adult indigenous volunteers from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 36 publications
(51 reference statements)
2
25
0
4
Order By: Relevance
“…The MetS prevalence found in this study was higher than that reported in other studies of health-care workers (29.5–40%) [ 3 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. However, it was similar to the prevalence observed in the general population of Mexican-Amerindians (50.3%) [ 50 ]. Discrepancies between the overall prevalence of MetS in this study and in the above-mentioned studies may be attributable to the fact that most of the subjects in this study were older than 40 years old and presented high obesity rates.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The MetS prevalence found in this study was higher than that reported in other studies of health-care workers (29.5–40%) [ 3 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. However, it was similar to the prevalence observed in the general population of Mexican-Amerindians (50.3%) [ 50 ]. Discrepancies between the overall prevalence of MetS in this study and in the above-mentioned studies may be attributable to the fact that most of the subjects in this study were older than 40 years old and presented high obesity rates.…”
Section: Discussionsupporting
confidence: 86%
“…However, more studies are needed to elucidate the function of this gene and its impact on MetS and its mainly component HDL-c in the Mexican population. The Mexican population has one of the highest rates of low HDL-c levels and prevalences of MetS worldwide [ 3 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…(1,2,4,5,(9)(10)(11) Overall, Mexicans have a high burden of chronic diseases such as diabetes, high blood pressure, and chronic kidney disease, although the prevalence of some of these diseases seems to be higher among Indigenous peoples. (13)(14)(15)(16)(17) Our results show that a higher proportion of Indigenous peoples in almost all age groups, in both genders, and with comorbidities died in our sample, which suggests access to care and the quality of care might play a role on the impact of COVID-19 among Indigenous peoples.…”
Section: Discussionmentioning
confidence: 81%
“…Similar to previous studies, we found that age, gender, and the presence of comorbidities are important predictors of death among patients with COVID-19 [ 1 , 2 , 4 , 5 , 9 11 ]. Overall, Mexicans have a high burden of chronic diseases such as diabetes, high blood pressure, and chronic kidney disease, although the prevalence of some of these diseases seems to be higher among Indigenous peoples [ 14 18 ]. Our results show that a higher proportion of Indigenous peoples in almost all age groups, in both genders, and with comorbidities died in our sample, which suggests access to care and the quality of care might play a role on the impact of COVID-19 among Indigenous peoples.…”
Section: Discussionmentioning
confidence: 99%